Evaluation of antibacterial and antifungal properties of selected mouthwashes: in vitro studies - Olejnik Ewa (Sciendo, 2021)
Introduction. Mouthwashes should include antimicrobial compounds to inhibit microorganism multiplication, thus the formation and development of dental plaque.